The investigative competences of the Bolivarian Primary Education teacher (Revista Electrónica REDINE, 2020)
The purpose of this essay is to present a reflection on the importance of the investigative competences of the primary education teacher from learning to be, learning to know, learning to live and learn how to do it. Delors (1996) are competences to develop what Throughout the life of the human being in order to achieve success as professionals, human beings and contribute to raising the quality of education. For today's society requires updated teachers to face the challenges that arise and thus be able to propose alternative solutions to the transformational moments experienced by Venezuelan society. The development of research competencies in the 21st century research teacher, proposes a change from the paradigm of the master transmitter of knowledge to a creative teacher and researcher, transformer of the educational environment, proposing strategies for solving the problematic situations of the classroom, in the context community, environmental and its pedagogical practice to achieve educational quality.
Keywords: competencies; investigatory; teacher